Validation of a blast induced neurotrauma model using modified Reddy tube in rats: A pilot study - Bhat, Dhananjaya I.; Shukla, Dhaval; Mahadevan, Anita; Sharath, N.; Reddy, K.P.J. (Indian Journal of Neurotrauma, 2014)
Blast induced neurotrauma (BINT) is becoming increasingly prevalent. However the pathophysiology has not been elucidated. In animal models blast injury is mimicked by exposing the animals to shock waves produced by shock tubes or by exposing them to open field explosions. We have tried to validate a custom made handy, indigenous blast tube in producing blast injury in a rodent model.Fifteen rats were subjected to increasing peak pressure blast waves using a modified Reddy blast tube. The pressure recordings were in keeping with the classic Friedlander waveform and were highly reproducible. One rat died immediately following exposure to the blast. At the end of 2 weeks all the live rats were sacrificed and subjected to histopathological examination.The pathology revealed neuronal degeneration and axonopathy in the cortex, cingulum, hippocampus, thalamus, brain stem and cerebellum with the severity of injury increasing with increasing blast pressure. These findings were consistent with that reported in the literature.We have thus successfully validated the blast tube for production of BINT. The tube is handy, easy to use and can be made widely available for furthering the research in the field of BINT.
Keywords: Blast; Neuronal degeneration; Neurotrauma; Rat model; Reddy tube